Pengembangan Laporan Keuangan Rukun Tetangga : Analisis Bibliometrik Menggunakan Software VOSViewer (2019-2023) - Sandra Dwi Maharani Oktafiana; Yuhertiana, Indrawati (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2024)
Rukun Tetangga (RT) is the lowest level service unit as an extension of the government that is obliged to provide accountability. The literature on neighborhood accountability is minimal and only a few reviews have been conducted to study the relevant subject. The main objective of this research is to highlight the development of neighborhood accountability through financial statements by conducting a bibliometric review of literature derived from the Google Schoolar database. The results showed that there were 500 published articles related to financial statements. Of the 500 published articles with the keywords